Reading the Geology of Canada: Geological Discourse as Narrative - Eagan, William (Scientia Canadensis, 1992)
ABSTRACTThis article suggests that Sir William Logan's Geology of Canada can be read as a narrative describing the past dynamic changes that shaped the present structure of the earth. The author also suggests, since the foundation of nineteenth century geology was a bio-stratigraphic consensus that combined stratigraphy and the fossil record, that the use of a narrative offered Logan a dynamique method for presenting his central argument.